Is APBM A Better Device For Monitoring Pregnancy Than Sphygmomanometer? - H.H. Kasim; M.A. Masri; N.A. Noh; A. Mokhtar; R.H. Mokhtar (Elsevier, 2024)
International Journal of Cardiology Volume 297, Supplement, December 2019, Pages 25-26